Synergistic effects of 5-fluorouracil in combination with salinomycin promoted ferroptosis via inhibiting SLC7A11/GPX4 in colorectal cancer - Wang, Can; Wang, Junyang; Xing, Fei; Liu, Ning; Wang, Xudong (Frontiers in Oncology, 2025)
Purpose5-Fluorouracil (5-FU) resistance is considered to be a possible reason for the failure of conventional drug treatment of colorectal cancer (CRC). Recently, salinomycin (SAL), as a selective inhibitor of cancer stem cells (CSCs), has been used to sensitize and attenuate a variety of solid tumor chemotherapy drugs. In our study, our goal was to combine SAL with 5-FU to explore not only whether there is an increase in sensitivity of CRC to 5-FU but also the molecular mechanism involved in enhancing 5-FU sensitivity and promoting tumor cell chemotherapeutic death.MethodsComboSyn software was used to study whether dual drug combinations synergistically promote each other and their dosage. CCK8, EdU, and Annexin V/PI assays were used to study the cell proliferation and apoptosis of SW480 and HCT116 cells in response to SAL single-drug and dual-drug co-treatment. Cell cycle staining was used to assess cycle arrest. Wound healing and migration and invasion experiments were used to identify changes in migration and invasion capabilities under the influence of different drugs. Transcriptome sequencing is used to explore the molecular mechanisms of drugs. Reactive oxygen species (ROS) fluorescence staining and malondialdehyde (MDA) level measurement were used to confirm the changes in ferroptosis levels of SW480 and HCT116 cells after drug treatment. Nude xenograft mice were used to detect antitumor in vivo. Changes in the protein level expression of ferroptosis GPX4 and SLC7A11 were also determined in the treated cells.ResultsSAL alone and in combination with 5-FU were found to significantly increase cell mortality and apoptosis. At the same time, our results show that the combination of SAL and 5-FU not only inhibits the proliferation, migration, and invasion of CRC cell lines in vivo and in vitro, but also promotes ferroptosis of CRC cell lines by downregulating the expression of GPX4 and SLC7A11. It may provide more and novel solutions and treatment perspectives for 5-FU or other drug-resistant chemotherapy strategies for patients with CRC.ConclusionsSAL inhibits CRC, whose effect is achieved by reducing GPX4 and SLC7A11 protein levels to mediate ferroptosis activation in collaboration with 5-FU.